Lac Cultivation in India: II. Lac Prices at Growers Level - Sircar, Sumita; Saha, Amit Kumar; Sindhu Veerendra, H. C.; Kujur, Ruby S. (Indian Forester, 2013)
Lac is produced by an insect Laccifer lacca (Synonym: Kerria lacca; super family Coccoidea). There are about 160 tree species that serve as host but mainly reared on Zizipus mauritiana, Schleichera oleosa and Butea monosperma in India. Two strains- kusumi and rangeeni are prominently cultivated in India and both differ in their seasonal cycle. The variation observed in bimonthly prices was ascribed to seasonal harvesting rather than prices themselves. Prediction of price movement of mean sticklac was carried out for next five years by regression method on a linearity between export performance and current market dynamics indicates steady prices for sticklac in local markets however, with a slight decrease in prices at later stages (R2= 0.53). Similarly, local market fluctuations on current trend scenario will remain in future also (R2= 0.44). Regression of exported lac products predicted a steady export performance for next five years assuring retention of current domestic price trend. The demand in international markets for lac products will remain steady and may slightly increase due to awareness of consumers to use natural products in place of synthetic products. It is suggested that a support pricing policy may be adopted for lac-support price on annual basis.